EVALUASI KINERJA CUSTOMER SERVICE PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK CABANG SIDENRENG-RAPPANG - Syafrimansyah Syafrimansyah; Rusli Siri; Syarifuddin Arief (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
This study aims to determine the performance standards of Customer Service at PT Bank BRI Sidenreng Rappang Branch. The type of research carried out is qualitative or in the form of descriptions in the form of explanations from sources related in this study so that accurate data can be obtained on the problem and then analyzed so that conclusions can be drawn. The design of this study was to review the documents and standard operating procedures of the customer service frontliner at PT Bank Rakyat Indonesia Cab Sidenreng-Rappang and other sources of library data. Based on the results of research and discussion of researchers on the evaluation of customer service performance, researchers can conclude that the customer service of BRI Sidrap Branch Office has carried out well and fully responsible for all its duties in accordance with the applicable BRI Kanca Sidrap Company Operational Standards (SOP). For the obstacles experienced by customer service in meeting service quality targets, the researchers conclude that there are three obstacles, namely in terms of the network, product knowledge that is always updated, and the character of customers who are not always the same.